Impact of Scarcity on Schooling - Khanal, Jagadishwar (Journal of Balkumari College, 2019)
This article examines the effects of poverty on education. Many different aspects contribute to a community becoming disadvantaged such as deindustrialization, high unemployment rates, untreated mental health, and violent crimes. Disadvantaged communities rural and urban face many issues. These issues include broken-down housing, lack of access to professional services, and most importantly inferior education. The education is inferior for a number of reasons; students are showing up to educational institute with numerous problems that the teachers are unable to account for through instruction. The educational institute facilities face structural inadequacies which have been proven to have an effect on the quality of instruction. The teachers in the educational institutes, while qualified, are often times not supported by educational institute administration. Educational institute administrators are busy with their own issues in determining what areas to allocate their limited budget. Poverty is a vast and complex issue that plagues communities in a seemingly endless cycle. However, working together to find effective ways of solving issues caused by poverty, the future can become a brighter for Nepalese youth growing up in poor communities.